Empirical Correlation of the Morphology of Coiled Carbon Nanotubes with Their Response to Axial Compression. (2nd February 2014) - Barber, Jabulani R.; Boyles, Jeffrey S.; Ferri, Aldo A.; Bottomley, Lawrence A.
Abstract : The mechanical response of thirteen different helical multi-walled carbon nanocoils to axial compression is reported. Each nanocoil was attached to the apex of a cantilever probe tip; its dimensions and orientation relative to the tip apex were determined with scanning electron microscopy. The atomic force microscope was employed to apply a cyclic axial load on the nanocoil. Its mechanical response was determined by simultaneous collection of the thermal resonance frequency, displacement, and oscillation amplitude of the cantilever-nanotube system in real time. Depending upon compression parameters, each coil underwent buckling, bending, and slip-stick motion. Characteristic features in the thermal resonance spectrum and in the force and oscillation amplitude curves for each of these responses to induced stress are presented. Following compression studies, the structure and morphology of each nanocoil were determined by transmission electron microscopy. The compression stiffness of each nanocoil was estimated from the resonant frequency of the cantilever at the point of contact with the substrate surface. From this value, the elastic modulus of the nanocoil was computed and correlated with the coiled carbon nanotube's morphology.